Applications of nuclear physics in medical diagnostics: A comparative study between SPECT and PET - Amani Shyaa Jebur (Academia Open, 2026)
Nuclear physics has fundamentally transformed medical diagnostics through Single Photon Emission Computed Tomography (SPECT) and Positron Emission Tomography (PET), which provide functional and physiological information beyond conventional imaging modalities. This study conducts a comprehensive comparative analysis of SPECT and PET by examining their nuclear physics principles, technical instrumentation, image quality parameters, and clinical applications. Employing systematic literature review methodology, the research synthesizes peer-reviewed articles from major scientific databases published between 2015 and 2025. The analysis reveals that PET demonstrates superior spatial resolution (4-7 mm versus 8-12 mm), enhanced sensitivity (1-2% compared to 0.01-0.03%), and greater quantitative accuracy due to coincidence detection and higher photon energy (511 keV). Conversely, SPECT maintains advantages in cost-effectiveness, radiotracer accessibility through on-site synthesis, and longer half-lives suitable for extended protocols. This research integrates physical, instrumental, and patient-dependent factors influencing image quality while exploring emerging developments including hybrid imaging and artificial intelligence applications. The findings establish evidence-based criteria for modality selection, emphasizing the complementary nature of these techniques in advancing precision diagnostics across oncology, cardiology, and neurology.Keywords : Nuclear Medicine Imaging, SPECT Modality, PET Technology, Radiotracer Applications, Gamma Photon Detection, Medical DiagnosticsHighlight : PET demonstrates superior spatial resolution (4-7 mm) and sensitivity (1-2%) compared to SPECT's performance metrics. Hybrid imaging systems combining PET-CT achieve widespread clinical acceptance, particularly enhancing oncology diagnostic capabilities. Collimator geometry primarily limits SPECT resolution (8-12 mm), while coincidence detection enables PET's improved quantitative accuracy.